Sentidos experienciados nos processos formativos de/com professoras alfabetizadoras da Rede Municipal de Educação de Cuiabá de 2019 a 2022 - Ferreira, Josemeire do Nascimento (2023)
This dissertation walks through the discussions that involve the professional development of literacy teachers from the Municipal Education Network of Cuiabá. Here, we seek to present reflections on the meanings experienced by them, in their formative processes experienced from 2019 to 2022. This time frame is permeated by some changes in educational policy with the implementation of the BNCC (National Common Curricular Base), the PNA (National Literacy Plan), the construction of the Municipal Education Policy of Cuiabá and the constitution of the ProAC (Cuiabano Literacy Program), as well as atypical situations generated by the Covid-19 pandemic. The methodology is structured in narrative research, understood here as the phenomenon to be studied (the narrative) and also as the study method. Since we reflect and think narratively about the reality experienced and perceived by the investigated subjects, in an understanding that the narrative is permeated by social, subjective and temporal issues. The research will be carried out through document analysis, bibliographic review on the chosen theoretical path and composition of field texts from written narrative and in-depth narrative interview. The object of the research encompasses the understanding of continuing education, now conceived as one of the moments of professional development. In this way, the perspective of professional development is formulated as a continuous and permanent movement that takes place in different spaces and in different relationships. In addition, we will discuss that teaching knowledge is constituted in different ways, being initial training, knowledge and perception about the profession and experiences related to it. And to direct the gaze on the investigation, we treat the concept of experience understood here as something that modifies and transforms. To complete, in order to base the narrative method, we make use of the narrative research that corresponds to the method and phenomenon of the research. The research participants are 6 effective teachers from the Municipal Education Network of Cuiabá, with an average of 6 years of experience with literacy classes. In close dialogue with the narratives, we established some axes for understanding. The first consists of building the identity process of a literacy teacher; the second approaches the meanings from the experienced formations; the third contemplates the relationship between constructed meanings and developed practices. From this path taken, some meanings constructed by the teachers were perceived in their narratives. In a very present and notorious way is the relationship between theory and practice; the subjectivity, the selectivity and the yearnings that motivate the search for formation and the redefinition of the practices. Thus, these senses allow us to interact with the teachers and deduce valuable information from the constitutive process, as something that transforms and forms us, in a temporal, social and subjective relationship.